DESAIN DIDAKTIS KONSEP BANGUN RUANG MATERI KUBUS UNTUK KELAS V SEKOLAH DASAR - Maya Puspitasari; Nyiayu Fahriza Fuadiah; Murjainah M. (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2021)
This study aim to make a didactical design on the concept of building a cube material in the 5th elementary school based on Learning Obstacle (LO). The approach used in this study is a qualitative approach with the DDR (Didactical Design Research) method which includes three stages, namely prospective analysis, metapedadidactic analysis, and retrospective analysis. The prospective analysis stage identifies the Learning Obstacles experienced by students in the cube material, including: 1) Ontogenic Obstacles, such as a lack of student interest in learning mathematics, only 50% of students in the class who like learning mathematics and lack of student mastery in prerequisite material; 2) Didactical Obstacle, namely the learning method used is still monotonous, the learning media is less varied and the teaching materials used are incomplete; 3) Epistemological Obstacle, namely students do not understand how to determine the volume of a cube, students do not understand problem solving strategies related to unit cubes. Based on the findings of LO, a Hypothetical Learning Trajectory (HLT) was compiled which was then designed a hypothetical didactic design on the concept of building cube material which includes four learning objectives, namely determining the area of ​​a square, analyzing the elements of a cube, determining the volume of a cube, and completing problems related to the volume of a cube using the unit volume. The didactic design is applied by the method of snowball throwing and flashcard games. After the didactic design was implemented, the results of the LO of the final identificational test were decreased compared to the LO of the diagnostic test. The didactic design is one of the effective learning alternatives in reducing the appearance of LO in the concept of building a cube material in the 5th elementary school.